2011
DOI: 10.4097/kjae.2011.61.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of preoperative versus intraoperative dexamethasone after laparoscopic cholecystectomy with multimodal analgesia

Abstract: BackgroundPain after laparoscopy is multifactorial and different treatments have been proposed to provide pain relief. Multimodal analgesia is now recommended to prevent and treat post-laparoscopy pain. Dexamethasone is effective in reducing postoperative pain. The timing of steroid administration seems to be important. We evaluated the analgesic efficacy of preoperative intravenous dexamethasone 1 hour before versus during laparoscopic cholecystectomy with multimodal analgesia.MethodsOne hundred twenty patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The results are similar with studies conducted by Fukami et al [8] and Lim et al [9] The mechanism of pain relief by dexamethasone is mainly provided by peripheral suppression of phospolipase enzyme, thereby significantly decreasing the products of cyclooxygenase and lipooxygenase pathways in the inflammatory response [8,10]. Additionally dexamethasone reduced bradykinin which reinforces pain in the inflamed tissues and operated area, and also the decreased concentration of nerve proteins secreted from the peripheral nerve system are involved in the analgesic effect [11].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results are similar with studies conducted by Fukami et al [8] and Lim et al [9] The mechanism of pain relief by dexamethasone is mainly provided by peripheral suppression of phospolipase enzyme, thereby significantly decreasing the products of cyclooxygenase and lipooxygenase pathways in the inflammatory response [8,10]. Additionally dexamethasone reduced bradykinin which reinforces pain in the inflamed tissues and operated area, and also the decreased concentration of nerve proteins secreted from the peripheral nerve system are involved in the analgesic effect [11].…”
Section: Discussionsupporting
confidence: 87%
“…With use of steroids complication such as delays recovery, postoperative infection, glucose intolerance and gastric mucosa ulcer can occur [9]. Sauerland et al [16] reported in their meta analysis that there was no significant increase in complications when they used 15-30 mg.kg -1 of methylprednisolone in one dose which is fifty times the amount of dexamethasone used in our study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…There is a report that giving local anesthetic [9], removing residual carbon dioxide [8], preemptive analgesia [10] and dexamethasone [3] are effective and recently multimodal analgesia using all of methods written above is recommended because it is more effective [3]. We reported that such multimodal analgesic method was effective for postlaparoscopic pain control [4]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, multimodal analgesia consisted of incisional local anesthetics, NSAID, dexamethasone, removing residual carbon dioxide, and postoperative opioid. We reported that such multimodal analgesic methods were effective for post-laparoscopic pain control [4]. …”
Section: Introductionmentioning
confidence: 99%